2004
DOI: 10.3149/jms.1301.25
|View full text |Cite
|
Sign up to set email alerts
|

“Why Can't a Man Be More like a Woman?”: Marital Status and Social Networking of Older Men

Abstract: Research indicates older lone men have an elevated risk of social isolation, but there has been little recognition of the way in which marital histories lead to the growth or attenuation of family bonds. First analysed is data from General Household Survey, a national probability based cross-sectional survey, published annually, which included a module on social relationships in 1994 and 1998. Also, interviews with 85 older married, widowed, divorced and never married men revealed that much importance was atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 33 publications
3
31
1
Order By: Relevance
“…In most discourses one can be masculine and one can be old, but not both. As much as femininity has been a boundarydefining yardstick for what masculinity is not, for the past two centuries "old" has also been incorporated as a cultural gauge for what masculinity is not (KIMMEL, 1997;THOMPSON, 2004;DAVIDSON, 2004). Normative masculinity became and remains embodied by middle-aged and younger men, both in mass culture and in men's studies.…”
Section: Ways To Understand Age Discrimination and Ageismmentioning
confidence: 99%
“…In most discourses one can be masculine and one can be old, but not both. As much as femininity has been a boundarydefining yardstick for what masculinity is not, for the past two centuries "old" has also been incorporated as a cultural gauge for what masculinity is not (KIMMEL, 1997;THOMPSON, 2004;DAVIDSON, 2004). Normative masculinity became and remains embodied by middle-aged and younger men, both in mass culture and in men's studies.…”
Section: Ways To Understand Age Discrimination and Ageismmentioning
confidence: 99%
“…Ten found a significantly larger difference in the prevalence of loneliness between single and married men than they did between single and married women (27,28,34,37,38,(51)(52)(53)(54)(55), and two also suggested that single men are lonelier than those in unmarried romantic relationships (51,56). The findings from seven qualitative studies further emphasised the particular importance of romantic relationships to men (40,42,46,(57)(58)(59)(60). As one man stated after the death of his wife, "all that intimacy goes and there is nothing to replace it" (59, p426).…”
Section: Study Characteristicsmentioning
confidence: 95%
“…Firstly, men did seem to consider a romantic partner the first, and primary, person for meaningful social interaction: 'we [men] do not talk like I'd talk with my wife' (46, p1252). Secondly, men's social networks were often found to be limited and dependent on their spouse (42,59,60). For instance, when discussing services aiming to alleviate loneliness, one man stated:…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, men who relocated to an age-restricted, planned community reported gains in terms of finding persons to provide emotional, practical, and illness support, but women in the same setting reported no gains or losses (Waldron, Gitelson, & Kelley, 2005). Davidson (2004) noted that older men take their cues from their partners (wives or girlfriends) in social settings, but may resist forging intimate bonds because of stereotypical gender roles (i.e., being strong, dispensing advice and material help) to which they are accustomed. We argue that although older men want socialization opportunities and supportive networks, they deny their needs for emotional support because of gender identity and their perceptions of masculine roles.…”
Section: Gender Differences In Social Engagementmentioning
confidence: 97%